Improving Taxpayer Compliance Through Assistance in Submitting Annual Income Tax Returns for the 2024 Tax Year and Education on the Coretax Application for Government Agencies - Galela, M. Ridhwan; Widiastuti, Budiasih; Supriyadi (Journal of Governance, Taxation and Auditing, 2026)
Compliance with Annual Tax Return (SPT) reporting remains a challenge in Indonesia's self-assessment system, primarily due to limited taxpayer understanding and adaptation to updates to the tax administration system, including the implementation of Coretax. The Community Service Program through the 2025 Tax Volunteer Program at the Pondok Aren Tax Office (KPP Pratama) is designed to improve compliance with Annual Income Tax Return (SPT) reporting for the 2024 Tax Year while providing education on the use of the Coretax application for government agency taxpayers. The program is implemented through stages of volunteer recruitment, capability mapping and training, assistance in filling out and reporting SPTs via e-Filing, assistance for taxpayers on the DSPT list, Coretax education for treasurers/agencies, and publication of tax education through social media. The implementation results show the collection of 99 student volunteers and 59 lecturer volunteers divided into 20 teams, with SPT assistance carried out offline in the period from the end of February to March 2025. Coretax education for government agencies also helps overcome feature constraints and understanding the reporting process in the new system. Overall, this program contributes to improving tax return reporting assistance services and strengthening tax literacy, and is worthy of continuation as ongoing support for Coretax adaptation.